2019
DOI: 10.1111/liv.14209
|View full text |Cite
|
Sign up to set email alerts
|

CONTROL: A randomized phase 2 study of obeticholic acid and atorvastatin on lipoproteins in nonalcoholic steatohepatitis patients

Abstract: Background & Aims Nonalcoholic steatohepatitis (NASH) is a chronic and severe form of nonalcoholic fatty liver disease that can progress to cirrhosis and hepatocellular carcinoma and is a risk factor for cardiovascular disease. Although NASH has no approved treatments, obeticholic acid (OCA), a synthetic bile acid and farnesoid X receptor (FXR) agonist, was shown to improve histological features of NASH and fibrosis. Considering that FXR activation influences plasma lipoprotein concentrations, the Combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 31 publications
1
83
0
3
Order By: Relevance
“…136 Results revealed that OCA increased mean LDL-C, mostly attributable to an increase in large LDL. 136 More importantly, the study showed that the lowest available dose of atorvastatin was able to reverse the OCA-mediated increase in LDL-C to below baseline levels. However, atorvastatin did not reverse the OCA-mediated decrease in HDL-C. showed that initiation of a statin in NGM282-treated patients resulted in a rapid decline in plasma lipid levels (Figure 3), showing that the increase in LDL-C is related to the LDL receptor and that statins can reduce the increased LDL-C observed with NGM-282 treatment.…”
Section: Farnesoid X Receptor Agonists and Fibroblast Growth Factormentioning
confidence: 91%
“…136 Results revealed that OCA increased mean LDL-C, mostly attributable to an increase in large LDL. 136 More importantly, the study showed that the lowest available dose of atorvastatin was able to reverse the OCA-mediated increase in LDL-C to below baseline levels. However, atorvastatin did not reverse the OCA-mediated decrease in HDL-C. showed that initiation of a statin in NGM282-treated patients resulted in a rapid decline in plasma lipid levels (Figure 3), showing that the increase in LDL-C is related to the LDL receptor and that statins can reduce the increased LDL-C observed with NGM-282 treatment.…”
Section: Farnesoid X Receptor Agonists and Fibroblast Growth Factormentioning
confidence: 91%
“…POISE study data showed that three-year OCA treatment reduced or stabilized hepatic collagen deposition and ductular injury in PBC patients with cirrhosis (69). The Combination OCA and Statins for Monitoring of Lipids (CONTROL) clinical trial study found increased LDL in NASH patients treated with OCA (5, 10, or 25 mg) indicating altered lipid metabolism (73). The observed increase in LDL cholesterol was reduced in NASH patients concurrently treated with OCA and atorvastatin, a statin utilized to reduce endogenous cholesterol production (73).…”
Section: Bile Acid Receptor/transporter Agonists and Antagonistsmentioning
confidence: 99%
“…The Combination OCA and Statins for Monitoring of Lipids (CONTROL) clinical trial study found increased LDL in NASH patients treated with OCA (5, 10, or 25 mg) indicating altered lipid metabolism (73). The observed increase in LDL cholesterol was reduced in NASH patients concurrently treated with OCA and atorvastatin, a statin utilized to reduce endogenous cholesterol production (73). The authors noted that these two drugs were well-tolerated when utilized together, addressing the observed increase in LDL cholesterol following OCA treatment in NASH patients, but remained inconclusive with respect to the combinatorial effect on hepatic injury (70,73).…”
Section: Bile Acid Receptor/transporter Agonists and Antagonistsmentioning
confidence: 99%
“…OCA-induced increases in LDL-C levels in NASH patients were mitigated with atorvastatin. 17 A phase 3 trial of OCA in NASH patients with cirrhosis is now ongoing (REVERSE trial). The REVERSE trial will be carried out at sites in North America, Europe, Australia, and New Zealand.…”
Section: Farnesoid X Receptor Ligandmentioning
confidence: 99%
“…This phase 2, multicenter, RDBPCT evaluated the effect of OCA and the subsequent addition of statin therapy, on lipoprotein metabolism in patients with NASH with fibrosis stage 1–4, but no evidence of hepatic decompensation. OCA‐induced increases in LDL‐C levels in NASH patients were mitigated with atorvastatin . A phase 3 trial of OCA in NASH patients with cirrhosis is now ongoing (REVERSE trial).…”
Section: Introductionmentioning
confidence: 99%